Selection of the Best Mathematical Model for Mapping Sea Surface Temperature on Jember Coast with Aqua Modis Satellite Imagery Data 2020 - Hendrata Wibisana; Femmy Kindanti; Bagas Aryaseta (Future Science, 2022)
Sea Surface Temperature (SST) is a parameter of water quality in the oceans, especially in coastal areas. This research was conducted on the Jember Coast of East Java to obtain the best mathematical model and map the distribution of sea surface temperature (SST). This research method uses sea surface temperature analysis using data from Aqua Modis satellite image data level 2 in April 2020 which is analyzed by geographic information system (GIS) analysis so that the results obtained are the distribution of sea surface temperature (SST). From the results of processing satellite imagery in Jember Coast, it can be concluded that the best mathematical model comes from the 412 nm channel with the mathematical model being Logarithmic with the equation: y = 0.1631ln(Rrs_412) + 31,331 and R2 = 0.0241.